Space charge-limited conduction in Ag/p-Si Schottky diode - Yakuphanoğlu, Fahrettin; Tugluoglu, Nihat; Karadeniz, S. (Elsevier Science Bv, 2007)
The space charge-limited conduction mechanism in Ag/p-Si Schottky diode was investigated at range of 175-275 K temperatures and detail information about low-temperature conduction mechanism of the Schottky diode could be obtained. Current-voltage characteristics and the power-law dependence was found to be governed by space charge-limited currents. In this conduction mechanism, the current increases superlinearly in the diode, i.e, I proportional to V-m. The I-V curves in the reverse direction at different temperatures are taken and interpreted via both Schottky and Poole-Frenkel effects. Poole-Frenkel effect was found to be dominant in the reverse direction. The density of localized states was determined, as well through the SCLC theory. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Ag/p-Si; Schottky diode; space charge-limited conduction